Development and characterization of 11 microsatellite loci for the Mona Island iguana (Cyclura cornuta stejnegeri) (2008)
We isolated and characterized 11 microsatellite loci in the Mona Island iguana (Cyclura cornuta stejnegeri). Eleven loci exhibit moderate to high allelic diversity (two to 12 alleles, mean = 4.5) and polymorphism (mean observed heterozygosity, 0.56; range, 0.26 to 0.78) in 41 adults. This marker set has low probability of identity and high parentage exclusion power and will be suitable for studies of paternity, social organization and relatedness in this species.